2008
DOI: 10.1111/j.1537-2995.2008.01936.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression levels of CD47, CD35, CD55, and CD59 on red blood cells and signal‐regulatory protein‐α,β on monocytes from patients with warm autoimmune hemolytic anemia

Abstract: BACKGROUND:Animal models have shown that CD47-deficient mice develop severe autoimmune hemolytic anemia (AIHA) because the binding of red blood cell (RBC) CD47 to signal-regulatory protein (SIRP-a) on macrophages contributes to the inhibition of phagocytosis. In contrast, complement-inhibitory proteins such as CD35, CD55, and CD59 may protect RBCs against the lysis by complement. STUDY DESIGN AND METHODS:With the use of flow cytometric analyses, the expression of CD47, CD35, CD55, and CD59 on RBCs and of SIRP-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 22 publications
0
27
0
Order By: Relevance
“…2B, inset). Meanwhile, it has been suggested that the deficient expression of mCRPs, especially CD59, is associated with autologous cell destruction by complement attack in autoimmune disorders, such as autoimmune hemolytic anemia, systemic lupus erythematosus, autoimmune thrombocytopenia, and aplastic anemia (4,5,30), possibly resulting from NF-B dysfunction due to genetic mutation (31). In addition, mouse CD59 genetic deficiency promotes atherogenesis in animal models (32); similarly, this study revealed the pathogenic roles of CD59 in atherosclerosis, a chronic inflammatory and immune vascular disease (33).…”
Section: Discussionmentioning
confidence: 99%
“…2B, inset). Meanwhile, it has been suggested that the deficient expression of mCRPs, especially CD59, is associated with autologous cell destruction by complement attack in autoimmune disorders, such as autoimmune hemolytic anemia, systemic lupus erythematosus, autoimmune thrombocytopenia, and aplastic anemia (4,5,30), possibly resulting from NF-B dysfunction due to genetic mutation (31). In addition, mouse CD59 genetic deficiency promotes atherogenesis in animal models (32); similarly, this study revealed the pathogenic roles of CD59 in atherosclerosis, a chronic inflammatory and immune vascular disease (33).…”
Section: Discussionmentioning
confidence: 99%
“…Probably it is caused by phylogenetic divergence and species specificity at a biochemical and genetic level [9,13,16]. Also, one should not compare the RBC senescence in vivo and in vitro [16].…”
Section: Discussionmentioning
confidence: 99%
“…Some of important roles of CD47 are suspected for example to be regulation of the migration, proliferation, survival of blood cells and some processes of innate and adaptive immunity. As a receptor of protein thrombospondin-1, it influences NO role in regulation of blood pressure, vascular flow and haemostasis [9][10][11]. The aim of this study is to DOI: 10.5114/ceji.2013.35205 compare the CD47 expression on RBCs from "fresh" and "old" units with and without leucocytes.…”
Section: Introductionmentioning
confidence: 99%
“…We have recently reported a RBC alloantibody prevalence of 11.1% in Brazilian patients with true AIHA. 30 The clinical physician attending patients with AIHA should understand that the aforementioned aspects of pretransfusion compatibility testing on AIHA patients are complex, and thus consider that a longer period of time is necessary for the blood bank to perform the complete panel of immunohematological tests which are necessary to guarantee the best RBC product for transfusion.…”
Section: Barros Et Almentioning
confidence: 99%
“…1,26 The prevalence of RBC alloantibodies in patients with WAIHA ranges from 7.5% to 54% (Table 3). 17,23,[27][28][29][30][31][32][33] The majority of studies reporting on the high frequency of coexisting alloantibodies and autoantibodies mostly describe patients with serological positive results rather than with clinically confirmed WAIHA. We have recently reported a RBC alloantibody prevalence of 11.1% in Brazilian patients with true AIHA.…”
Section: Barros Et Almentioning
confidence: 99%